Inclusion of young people with disabilities in the future of work: forecasting workplace, labour market and community-based strategies through an online and accessible Delphi survey protocol - Arif Jetha; Kathleen A Martin Ginis; Emile Tompa; Monique A M Gignac; Dwayne van Eerd; Kay Nasir (BMJ Open)
Introduction The future of work is expected to transform the nature of work, create unique employment barriers for young people living with disabilities and disrupt pathways to better health. We present a Delphi survey protocol through which we aim to obtain future-oriented strategies that can improve the accessibility and inclusion of young people with disabilities in the future of work.Methods and analysis The Delphi survey will be conducted primarily online, over two rounds and in a format that is accessible to people living with disabilities. A diverse sample of subject matter experts (eg, policy makers, employment service providers, labour market experts) and participants with lived experience of a disability will be recruited using a purposive sampling strategy. All participants will be asked to complete both rounds of the Delphi survey. In the first round, open-ended questions will be asked about workplace, community-based or policy supports that can foster the inclusion of young people with disabilities in the labour market and that can also address specific future of work trends which span sociopolitical, economic, environmental and technological domains. In the second round of the survey, we will aim to build consensus; participants will be provided with a summary of specific strategies that correspond to the different future of work trends emerging from round one and will be asked to rank-order strategies according to their importance. Following the completion of the second round, consensus-based and future-focused recommendations will be generated that can support young people with disabilities in the world of work over the coming decades.Ethics and dissemination The study protocol has been cleared by the University of Toronto’s research ethics board (#40727). The study will identify future-focused support strategies that will be shared with people living with disabilities, policy makers and disability employment service providers through an integrated knowledge transfer and exchange approach.